2011
DOI: 10.1016/j.ejcts.2010.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of sternoclavicular joint infection

Abstract: Surgery was found to be curative with good results for those patients with SCJ infection that did not respond to a full course of intravenous antibiotic therapy. Surgical options include incision and drainage, curettage or SCJ resection. The type of surgical procedure depends on the radiological findings, presentation, severity of the infection and intra-operative findings. In our experience, complex muscle flap reconstruction was not necessary following SCJ resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 25 publications
0
34
0
6
Order By: Relevance
“…The authors therefore recommend joint resection if any of the following factors are noticed during the pre-operative diagnostic workup: signs of bony destruction, chest wall phlegmon or abscess, retrosternal abscess, mediastinitis or pleural spread [14]. Abu Arab et al used five grades of infection based on clinical and radiological criteria and derived from them a graduated algorithm for the therapeutic management of septic arthritis of the SCJ [7]. Using this grading system, Jang et al treated 22 patients with septic arthritis of the SCJ caused by staphylococcus aureus.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The authors therefore recommend joint resection if any of the following factors are noticed during the pre-operative diagnostic workup: signs of bony destruction, chest wall phlegmon or abscess, retrosternal abscess, mediastinitis or pleural spread [14]. Abu Arab et al used five grades of infection based on clinical and radiological criteria and derived from them a graduated algorithm for the therapeutic management of septic arthritis of the SCJ [7]. Using this grading system, Jang et al treated 22 patients with septic arthritis of the SCJ caused by staphylococcus aureus.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The closure of the wound after resection of the sternoclavicular joint infection seems to favor using myocutaneous flaps, as evidenced by the stronger studies [ 1 , 5 , 6 , 22 ]. The use of myocutaneous flap can help obliterate the dead space resulting from resection of the sternoclavicular joint.…”
Section: Reviewmentioning
confidence: 99%
“…As shown in Figure 1, most of the original articles on the surgical management of sternoclavicular joint infections came from the United States (11, 68%) [1,3,5,6,[12][13][14][15][16][17][18]. Two studies came from Asia (12.5%) [4,19], one was from Europe (6.25%) [20], and two were multi-national [21,22].…”
Section: Origins Of Included Articlesmentioning
confidence: 99%
“…In this study, patients with an elevated BMI may have been found to have worsened infections during operative exploration, necessitating a deferral to multiple operations in order to achieve adequate infection clearance and definitive closure. As mentioned, immunosuppression and chronic disease states are associated with SCJ infection [ 8 , 14 ]. We hypothesize that an elevated BMI may predispose a similar state and influence worsened infection in the context of SC osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%